The Synergistic Activity and Optimizing Doses of Tigecycline in Combination with Aminoglycosides against Clinical Carbapenem-Resistant Klebsiella pneumoniae Isolates - Parnrada Nulsopapon; Worapong Nasomsong; Manat Pongchaidecha; Dhitiwat Changpradub; Piraporn Juntanawiwat; Wichai Santimaleeworagun (MDPI AG, 2021)
Carbapenem-resistant Enterobacteriaceae (CRE), especially carbapenem-resistant Klebsiella pneumoniae (CRKP), are among the largest pathogenic threats to humans. The available antibiotic treatment options for combating CRKP are limited. Colistin-resistant Enterobacteriaceae (CoRE) have also been reported worldwide, including in Thailand. Therefore, this study aimed (1) to determine minimum inhibitory concentrations (MICs) and synergistic activities of antibiotics of CRKP, and (2) to determine the probability target of attainment (PTA) and cumulative fraction of response (CFR) using pharmacokinetic/pharmacodynamic (PK/PD) data. Clinical CRKP isolates were obtained from Phramongkutklao Hospital (June to November 2020). Broth microdilution and checkerboard techniques were used to determine the mono- and synergistic activities of antibiotics. Carbapenemase and mcr-1 genes were also identified by polymerase chain reaction (PCR). The optimal antibiotic regimens were evaluated using Monte Carlo simulations. Forty-nine CRKP isolates were collected, 40 of which were CoRKP strains. The MIC50 and MIC90 of tigecycline, amikacin, and gentamicin were 1 and 2 µg/mL, 4 and 16 µg/mL, and 0.25 and 4 µg/mL, respectively. None of any isolates expressed the mcr-1 gene, whereas blaOXA-48 (53.1%) and blaOXA-48 plus blaNDM (42.9%) were detected. Synergistic activity was observed in 8.2% of isolates for tigecycline combined with amikacin or gentamicin. Additive activity was observed in 75.5% of isolates for tigecycline-amikacin and 69.4% for tigecycline-gentamicin, and no antagonism was observed. High-dose antibiotic regimens achieved the PTA target. The general recommended dose of combination regimens began with 200 mg tigecycline and 25 mg/kg amikacin, or 7 mg/kg gentamicin, followed by 100 mg tigecycline every 12 h and 15 mg/kg amikacin or 5 mg/kg gentamicin every 24 h. In conclusion, tigecycline plus aminoglycosides might be a potential regimen against CRKP and CoRKP. The appropriate combination regimen based on MIC-based dose adjustment can improve optimal antibiotic dosing. Further research via clinical studies will be necessary to confirm these results.